The in vivo impact of MsLAC1, a Miscanthus laccase isoform, on lignification and lignin composition contrasts with its in vitro substrate preference - He, Feng; Machemer-Noonan, Katja; Golfier, Philippe; Unda, Faride; Möbus, Johanna; Zhang, Wan; Hoffmann, Natalie; Samuels, Lacey; Mansfield, Shawn D.; Rausch, Thomas; Wolf, Sebastian (BMC plant biology, 2019)
Understanding lignin biosynthesis and composition is of central importance for sustainable bioenergy and biomaterials production. Species of the genus Miscanthus have emerged as promising bioenergy crop due to their rapid growth and modest nutrient requirements. However, lignin polymerization in Miscanthus is poorly understood. It was previously shown that plant laccases are phenol oxidases that have multiple functions in plant, one of which is the polymerization of monolignols. Herein, we link a newly discovered Miscanthus laccase, MsLAC1, to cell wall lignification. Characterization of recombinant MsLAC1 and Arabidopsis transgenic plants expressing MsLAC1 were carried out to understand the function of MsLAC1 both in vitro and in vivo.
Gesehen am 07.02.2020